Prevalence of and mothers’ knowledge, attitude and practice towards glucose-6-phosphate dehydrogenase deficiency among neonates with jaundice: a cross-sectional study - Kasemy, Zeinab A (BMJ Open, 2020)
BACKGROUND: Neonatal jaundice (NNJ) is a frequent complication of glucose-6-phosphate dehydrogenase (G6PD) deficiency. OBJECTIVES: To estimate the prevalence of G6PD deficiency among neonates with jaundice and to assess mothers’ perception towards G6PD and NNJ. METHODS: A cross-sectional study was carried out on 487 ethnic Egyptian neonates with indirect hyperbilirubinaemia from June 2018 to July 2019. The collected data included maternal and neonatal characteristics. Laboratory investigations included serum bilirubin, reticulocyte count, ABO grouping, Rh typing and neonatal serum G6PD test. Mothers were interviewed individually using a structured, researcher-administered questionnaire to assess their perceptions of G6PD deficiency and NNJ. RESULTS: The prevalence of G6PD deficiency was 10.10%. Neonates with G6PD deficiency showed higher levels of serum bilirubin (p<0.001). Male gender, family history of G6PD deficiency and consanguinity were risk factors for G6PD deficiency (OR=4.27, 95% CI 1.66 - 10.99; OR=9.54, 95% CI 4.80- 18.95; OR=10.219, 95% CI 5.39 - 19.33, respectively). Mothers’ perceptions of NNJ and G6PD were low, with only 30% having good knowledge on NNJ and 17.10% on G6PD deficiency, 46.8% with positive attitude towards NNJ and 45.0% towards G6PD deficiency, and 29.9% with good practice towards NNJ and 19.9% towards G6PD deficiency. CONCLUSION: G6PD deficiency seems to be an important cause of NNJ. Mothers’ perceptions of both NNJ and G6PD deficiency were low. A mass health education programme on both of these diseases is needed to ensure better and early detection, good timing of treatment, and better prevention of the triggering factors to ensure better health for children.